The Impact Of Strength, Flexibility, And Motivation On Student Development In Elementary Education - Sari, Yayang Yulia; Yenes, Ronni; Handayani, Sri Gusti; Yendrizal, Yendrizal; Ockta, Yovhandra (STKIP Singkawang, 2024)
Research problem the number of students who get scores below the minimum completeness criteria in the material on forward roll ability at Elementary School of 01 Situjuah Batua. The purpose of the study is to determine the effect of arm muscle strength, abdominal muscle strength, torso flexibility and motivation on forward roll ability at Elementary School of 01 Situjuah Batua. Quantitative research method. Path Analysis approach. The population of students in grades IV, V and VI totaling 108 people. Stratified random sampling technique. Sample of 22 students, data collection on arm muscle strength with pushups, abdominal muscle strength with sit-ups, torso flexibility with the KAKU test, motivation using data collection using questionnaires and forward roll ability tests. Research results: (1) arm muscle strength has a direct effect on forward roll ability, sig value = 0.008 < 0.05, has an effect of 16.8%. (2) abdominal muscle strength has a direct effect on forward roll ability, sig value = 0.001 < 0.05, has an effect of 26.5%. (3) torso flexibility has a direct effect on forward roll ability, sig value = 0.011 < 0.05 has an effect of 13.2%. (4) motivation has a direct effect on forward roll ability, sig value = 0.033 < 0.05 has an effect of 9.4%. (5) arm muscle strength has an indirect effect on forward roll ability of 1.9%. (6) abdominal muscle strength has an indirect effect on forward roll ability of 3.1%. (7) torso flexibility has an indirect effect on forward roll ability of 1.4%. (8) Arm muscle strength, abdominal muscle strength, trunk flexibility and motivation have a simultaneous effect on forward roll ability, Rsquere value = 0.740 with probability (sig) = 0.000. If the sig value is <0.05, then these four variables have an effect on forward roll ability of 54.8%.